From ethnography to virtual reality: researching police-public interactions - Bradford, Ben (Introduction to policing research, 2024)
Interaction with the public is central to policing. Encounters between officers and victims, witnesses, suspects and, much more generally, ‘the public’, can be hugely consequential for all involved. They invoke questions of trust, legitimacy, cooperation and compliance as well as, all too often, issues of ethnic, racial and other forms disproportionality. Ultimately, they reveal the power of the state to intervene, sometimes forcibly, in people’s lives. Concentrating on interactions between police and people not yet formally ‘in’ a criminal justice process, this chapter sketches out the methods that have been used by criminologists and others to investigate such interactions, outlines the questions researchers have tended to ask, and discusses some of the challenges and pitfalls that confront them. To understand how policing unfolds in practice, and the relationship(s) between police and policed, we must attend to police-public interaction; but this is not necessarily an easy topic to research, and it presents a number of thorny methodological, epistemological and ethical challenges.